2009
DOI: 10.1111/j.1750-3841.2009.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Pasta with Unripe Banana Flour: Physical, Texture, and Preference Study

Abstract: Banana is a starchy food that contains a high proportion of undigestible compounds such as resistant starch and nonstarch polysaccharides. Products with low glycemic response such as pasta are considered favorable to health. The objective of this study was to use unripe banana flour to make spaghetti with low-carbohydrates digestibility and evaluate its physical and texture characteristics, as well as consumer preference. Formulations with 100% durum wheat semolina (control) and formulations with 3 semolina: b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 25 publications
2
41
1
1
Order By: Relevance
“…This pattern is related to the higher cooking loss values of the gluten-free spaghetti than the control spaghetti because the same cooking time (8 min) was used for all the samples. Agama-Acevedo et al (2009) reported similar results in spaghetti added with UPF. Los valores son la media ± error estándar.…”
Section: Texture Attributes Of Cooked Spaghettisupporting
confidence: 73%
“…This pattern is related to the higher cooking loss values of the gluten-free spaghetti than the control spaghetti because the same cooking time (8 min) was used for all the samples. Agama-Acevedo et al (2009) reported similar results in spaghetti added with UPF. Los valores son la media ± error estándar.…”
Section: Texture Attributes Of Cooked Spaghettisupporting
confidence: 73%
“…In general, the elasticity and chewiness did not change with the addition of UBWF, although an appreciable increase in the chewiness was observed with the addition of UBWF to the blend. The addition of UBF presented similar texture values for hardness, adhesiveness, and chewiness [31], but higher values of elasticity were obtained for the types of spaghetti with UBWF. The presence of non-starch polysaccharides in the peel could be responsible for these results.…”
Section: Cooking Testsmentioning
confidence: 82%
“…Cauvain (1998) estudou o endurecimento de produtos panificados congelados e sugeriu que algumas alte rações na textura desses produtos, tais como o aumento da dureza em pães devido à perda de água para a atmosfera e também devido à perda de água no processo de retrogradação do amido, estão atreladas à umidade. Agama-Acevedo et al (2009), pesquisando as propriedades físicas e a textura de macarrão (espaguete), enriquecido com farinha de banana verde, afirmam que a elasticidade e a mastigabilidade se alteraram com a adição de farinha de banana na massa. Esse aumento significativo também foi observado no presente estudo (Tabela 6).…”
Section: Resultsunclassified